TINJAUAN ATAS PERHITUNGAN, PEMOTONGAN DAN PELAPORAN WITHHOLDING TAX SYSTEM PPh PASAL 21 PADA SEKRETARIAT DPRD PROVINSI DKI JAKARTA - Sulistyani Dwi Pangestu (2020)
This final report discusses about The Review of Calculation, Deduction, And Reporting Withholding Tax System at the Provincial Parliament Secretariat of DKI Jakarta. Tax is one of the most important things that state relevancy for the state revenue in order to finance all state expenditure, both development or non-development one. one type of tax that greatly contributes to the receipt of state cash is the income tax. Experts are one of the elements of income tax article 21 as a professional service provider which is very much needed expertise in certain fields. The purpose of this Final Project Report is made to find out the calculation and collection system used also the implementation of article 21 income tax that carried out by the Provincial Parliament Secretariat of DKI Jakarta. based on the final of this report, it can be concluded that the Provincial Parliament of DKI Jakarta is implementing the withholding tax system as a system for collecting income as article 21 by experts. In accordance with Law No. 36/2008, the system is implemented for the calculation, deduction and reporting of income tax article 21.